1990
DOI: 10.1128/jcm.28.4.685-688.1990
|View full text |Cite
|
Sign up to set email alerts
|

Serological classification by monoclonal antibodies of Rickettsia tsutsugamushi isolated in Korea

Abstract: Antigenic types of 113 strains of Rickettsia tsutsugamushi isolated from Korean patients were analyzed by using murine polyclonal and monoclonal antibodies. The isolates can be classified in six groups according to their reaction to a panel of monoclonal antibodies. Nine isolates of group I were identified as the Gilliam serotype, and 13 isolates of groups Il and III were identified as the Karp serotype. There were two groups that were considered to be a mixture of groups I and II or groups I and III, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…The geographical distribution of the Boryong genotype was slightly higher in southern Korea than in mid-Korea, while the Gilliam, Karp and Pajoo genotypes were mainly distributed throughout the mid-region of Korea. These results were similar to those of several clinical studies [3], including our result from a study conducted between 2003 and 2005 (data not shown). These findings revealed that the geographical distribution of O. tsutsugamushi genotypes differs slightly according to endemic area.…”
supporting
confidence: 93%
“…The geographical distribution of the Boryong genotype was slightly higher in southern Korea than in mid-Korea, while the Gilliam, Karp and Pajoo genotypes were mainly distributed throughout the mid-region of Korea. These results were similar to those of several clinical studies [3], including our result from a study conducted between 2003 and 2005 (data not shown). These findings revealed that the geographical distribution of O. tsutsugamushi genotypes differs slightly according to endemic area.…”
supporting
confidence: 93%
“…The fixed cells were washed twice with 1 ml of ice-cold PBS and permeabilized by treating the cells with 1 ml of 0.2% Tween-20 for 15 min at 37 C. The permeabilized cells were washed twice with 1 ml of ice-cold FACS buffer (PBS containing 0.5% FBS) and labeled with antibodies for 30 min at 4 C in FACS buffer. The cells were incubated with monoclonal antibodies to O. tsutsugamushi (10) or gp96 (Santa Cruz Biotechnology Inc., Santa Cruz, Calif., U.S.A.). It subsequently reacted with FITC-labeled anti-mouse IgG or anti-goat IgG (Sigma Chemicals Co.).…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of 56-kDa genes of six strains, Gilliam, Karp, Kato, Kawasaki, Kuroki and Shimokoshi, were reported previously [9^11]. Sequences of the genes of Yonchon and Boryong strains isolated in South Korea have been reported in Korean studies [12,13], and the sequences of TA678, 686, 716 and 763 strains obtained in Thailand [4] and the Sxh 951 strain in China were cited from the GenBank. The sequencing of other strains in Table 1 was carried out in this study.…”
Section: Methodsmentioning
confidence: 99%